Aspirin-Induced Microscopic Surface Changes Stimulate Thrombopoiesis in Rat Megakaryocytes. (April 2014) - Kazama, Itsuro; Maruyama, Yoshio; Nakamichi, Satoshi
During the process of thrombopoiesis, invaginations of the plasma membrane occur in megakaryocytes. Since acetylsalicylic acid (aspirin), the most commonly used anti-inflammatory and antiplatelet drug, interacts with the lipid bilayers of the plasma membranes, this drug would affect the process of thrombopoiesis. In the present study, employing a standard patch-clamp whole-cell recording technique, we examined the effects of aspirin on delayed rectifier K + -channel (Kv1.3) currents and the membrane capacitance in megakaryocytes. Using confocal imaging of di-8-butyl-amino-naphthyl-ethylene-pyridinium-propyl-sulfonate (di-8-ANEPPS) staining, we also monitored the membrane invaginations in megakaryocytes. Aspirin suppressed both the peak and the pulse-end currents with a significant increase in the membrane capacitance. Massive di-8-ANEPPS staining after treatment with aspirin demonstrated the impaired membrane micro-architecture of megakaryocytes. This study demonstrated for the first time that aspirin induces microscopic surface changes in megakaryocytes. Such surface changes were thought to stimulate thrombopoiesis in megakaryocytes as detected by the increase in the membrane invaginations.